Of routes and corridors: Challenges and opportunities for Silk Road destinations in the southern Caucasus - Arne Schuhbert; Hannes Thees (Journal of Tourism, Heritage & Services Marketing, 2020)
Purpose: Under the title of Belt-and-Road-Initiative (BRI), China has launched a global development program, which spans many regions and sectors. Tourism initiatives in particular, can occupy an interlinking position between infrastructure and services, and between global and local projects. This paper addresses the problem of the global-local link by critically examining a case at the southern Caucasus, as tourism is considered as a key industry for economic diversification in all three countries examined. Methods: Based on a mixed qualitative and quantitative approach, the study is about critically investigating the current state of challenges and opportunities for tourism-induced, integrated regional development, with particular focus on potential obstacles for regional and national destination competitiveness. Results: Results reveal that the BRI offers a basis for export-diversification in tourism and non-tourism economic sectors. Azerbaijan has the potential to integrate BRI activities into its local economic system but depends highly on the development of the Trans-Eurasian Corridor and the readiness of local entrepreneurs and institutions to support and extend development initiatives. Implications: The implementation of the BRI offers a significant opportunity for many rural regions to proactively benefit from increasing tourism demand, by linking local initiatives and industries with tourism-related projects embedded in the BRI.
Keywords: L80; M10; Z33; 330; destination management; competitiveness; belt-and-road-initiative; new silk road